Inhibition Activity Of Black Cumin Toothpaste Contain With Detergent Compared With Black Cumin Extract Non Detergent To The Growth Of Supragingiva Plaque Bacteria - Masya, Resgita Nadila; Ulfah, Noer; Hadinoto, Maria Elisea Kiswantoro; Sugito, Bambang Hadi; Wahyudadi, Badai Septa; Setiawatie, Ernie Maduratna (Indonesian Journal of Dental Medicine, 2019)
Background: Plaque can inhibit the antibacterial activity of salivary function, which can damage the periodontal tissue. Several preventive measures can be done to control plaque, mechanically or chemically. Mechanical plaque control in combination with chemical plaqie control such as toothpaste can reduce plaque. The role of SLS in toothpaste which can facilitate plaque detachment from the tooth surface. Herbal toothpaste has been developed using herbal ingredients that have antibacterial properties as black cumin (Nigella sativa). The contents of black cumin, thymoquinone, thymol, and tannins, have been proven to be effective in inhibiting the growth of plaque bacteria. Purpose: This study aims to identify the inhibitory ability of black cumin toothpaste extract containing detergent compared to black cumin extract toothpaste without detergent on the growth of supragingival plaque bacteria. Methods: This research method of diffusion of wells on BHIB media was conducted in four research groups namely negative control, cumin paste with SLS, non SLS cumin paste, and SLS and carried out bacterial planting on MHA media. Next measure the diameter of the inhibition zone around the well. Results: There was a significant difference in each group against the inhibitory growth of supragingival plaque bacteria on the Oneway ANOVA test results (p <0.05) Conclusion: Black cumin extract toothpaste containing 2% of detergent has better inhibition against supragingival plaque bacteria than non cumin detergent 3% black cumin toothpaste.